A Criterion for Investing in Information - Owen, Joel (Management Science, 1968)
As the amount of money invoiced in a decision rises, so does the burden of making the decision. Thus, it is not surprising or rare that the question arises: should a study be instituted before the decision is made to lessen the risks involved? Of course, such a study will itself cost something depending on the cost of analyzing data, the number of people involved and the value of the information gathered. The decision maker is then confronted with two courses of action, to make a decision based on existing information or to institute a study program, i.e., to invest in information before making a decision. In this paper we develop a procedure by which the decision maker can choose between these alternatives.